2010
DOI: 10.1177/1076029609357738
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Protein Z Are Associated With HELLP Syndrome and its Severity

Abstract: Protein Z (PZ) was found to be associated with pregnancy complications. There are no data implying an association between hemolysis (H), elevated liver enzymes (EL), and low platelet counts (LP) (HELLP) syndrome and changes in plasma levels of PZ. The aim of this study is to investigate whether HELLP syndrome is associated with plasma concentrations of PZ. Protein Z levels in 29 women with HELLP syndrome were compared with 29 healthy, nulliparous and 25 normal pregnant women. The median PZ levels in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…126 One study found a correlation between lower PROZ levels and severity of HELLP syndrome (MIM: 614985), a complication of preeclampsia that stands for hemolysis, elevated liver enzymes, and low platelets and which occurs in 10-20% of preeclamptic pregnancies. 123,127 However, no study on PROZ or other clotting factors in preeclampsia has been successfully replicated, likely due to the extreme heterogeneity of the disease and the mix of populations studied.…”
Section: Discussionmentioning
confidence: 99%
“…126 One study found a correlation between lower PROZ levels and severity of HELLP syndrome (MIM: 614985), a complication of preeclampsia that stands for hemolysis, elevated liver enzymes, and low platelets and which occurs in 10-20% of preeclamptic pregnancies. 123,127 However, no study on PROZ or other clotting factors in preeclampsia has been successfully replicated, likely due to the extreme heterogeneity of the disease and the mix of populations studied.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a larger cross-sectional study found lower median levels of PROZ in preeclampsia outcomes but not IUGR or fetal demise (Erez et al, 2007). One study found a correlation between lower PROZ levels and severity of HELLP syndrome (a complication of preeclampsia that stands for haemolysis, elevated liver enzymes, and low platelets), which occurs in 10-20% of preeclamptic pregnancies (Haram, et al, 2014, Kaygusuz et al, 2011). However, no study on PROZ or other clotting factors in preeclampsia has been successfully replicated, likely due to the extreme heterogeneity of the disease and the mix of populations studied.…”
Section: Discussionmentioning
confidence: 99%
“…[37,38] Reduced PZ levels (<1 μg/mL) were linked with several pregnancy complications including fetal demise, preeclamsia, small-for-gestational age, intrauterine growth restriction, HELLP syndrome, and idiopathic recurrent miscarriage. [37][38][39][40][41] As is known, approximately 3% of the etiology of SSNHL is from the return of venous thromboembolism, which is obstructing the circulation in the labyrinthine artery. Inadequate and/or ineffective release of ZP/ZPI complex may also participate the pathophysiology of SSNHL, particularly in patients with idiopathic SSNHL.…”
Section: Discussionmentioning
confidence: 99%